Prevalência de indivíduos com níveis controlados de glicemia e pressão arterial na população nipo-brasileira de Bauru com diabetes mellitus e hipertensão arterial - Lopes, Ronaldo (2009)
This is a descriptive-quantitative study, that had as objective to determine the prevalence of the controlleds individuals of blood glucose and arterial pressure in diabetic and hypertensive nipo-brazilian population of Bauru, and to relate the use of medications with the levels of blood glucose and arterial pressure. The sample consisted of 1331 nipo-brazilians (1.th and 2.th generations), with aged 30-79 years. The results demonstrated that the use of medications to control its pathologies was insufficient to maintain in ideal levels the blood glucose and blood pressure (SAP and DAP).